Special Patient Populations for the Senior Medical Student Entering Surgery - Mara Antonoff; Courtney Green; Jonathan D'Cunha (Association of American Medical Colleges, 2014)
Abstract Introduction Postoperative management of special patient populations are important topics that are not uniformly covered in medical schools. We developed a competency-based course for incoming surgical interns incorporating didactics and small-group discussions, aimed to improve surgical intern readiness for management of special patient populations in the surgical setting. This resource includes materials intended to prepare senior medical students for management of special patient populations in the postoperative inpatient setting. This resource may be used by course directors for surgery preparatory classes/bootcamps, for independent study by individuals planning to matriculate into surgical residencies, or as a review source for those already in surgical training. Methods The materials provided include all instructor's blueprints, PowerPoint slides, and handouts for four separate sessions. A multiple-choice knowledge test is also included as one of these sessions. Results We found that course participants demonstrated marked improvement in task-specific confidence in all tasks from course beginning to end, supported by improved scores on written and technical skill examinations. Upon course completion, participants report high confidence in management of these patients, suggesting improved readiness for postoperative inpatient care. Further, course participants outperformed peers in all tasks 1 month into internship, with their performance advantage predictably dissipating into the third month of residency. Discussion We found that competency-based preparation for surgical internship utilizing the tools found within this resource resulted in objective gains in task-specific confidence and test performance at course conclusion, which translated to improved performance upon residency matriculation. While these materials were designed to meet the needs of new surgical house staff, the contents are easily generalizable to other medical specialties, and would prove useful for any trainee managing hospital inpatients.